An analysis of inclusive education practices in East Java Indonesian preschools - Yasin, Mohd Hanafi Mohd; Susilawati, Sinta Yuni; Tahar, Mohd Mokhtar; Jamaludin, Khairul Azhar (Frontiers in Psychology, 2023)
Poor access to quality education among preschool students in Indonesia is a cause for concern. To address this issue, the first step is to identify the current level of inclusive education practises in these institutions. Thus, this study is aimed at identifying the level of inclusivity of Indonesian preschools, particularly in East Java, from the perspective of education practitioners. This study employed a sequential explanatory mix design. A survey questionnaire and semi-structured interviews were utilised in collecting the data. A total of 277 education practitioners, including principals and teachers at the preschool level, were randomly sampled to answer the questionnaire. As interview respondents, 12 teachers and principals were recruited via purposive sampling. Generally, the findings indicated that community building for inclusive education was found to be at an average level (M = 3.418, SD = 0.323), whereas building inclusive values in preschools was found to be at a high level (M = 4.020, SD = 0.414). In support of this, the findings of the semi-structured interviews suggested that the school community was aware of the differences among students and that respecting each other was generally practised among the school community. However, poor community involvement to support inclusive education was a challenge in most Indonesian preschools. These findings are crucial for stakeholders and policymakers to continue promoting community awareness and supporting inclusive education in these institutions.